Effect of haverst season and ripening duration on the physico-chemical properties of new 'fuerte-type' avocando fruit selections during ripening - Munzhedzi, Mukondeleli (University of Limpopo, 2016)
The Agricultural Research Council-Institute for Tropical and Subtropical Crops (ARC-ITSC) is continuously developing new avocado selections, in order for the South African Avocado Industry (SAAI) to remain competitive in various international avocado markets. However, information on the response of some of these selections, including ‘Fuerte 2 and 4’, ‘BL1058’ and ‘H287’ to low temperature storage and ripening physiology, has not been investigated. Thus, the objective of this study was to evaluate the effect of harvest season and ripening duration on the physico-chemical properties of newly developed ‘Fuerte-type’ avocado fruit selections during ripening. ‘Fuerte-type’ avocado fruit were indexed for maturity using moisture content, thereafter harvested and stored at 5.5°C for 28 days during the 2014 and 2015 harvest seasons. The experiment comprised five treatments: control (commercial ‘Fuerte’), ‘Fuerte 2 and 4’, ‘BL1058’ and ‘H287’ arranged as a factorial in a completely randomised design (RCD) with 3 replicates. The treatment factors were: (i) 2 x harvest seasons, (ii) 5 x selections and (iii) 6 x ripening days. After withdrawal from low storage temperature, fruit were ripened at ambient temperature. During ripening, the following physico-chemical properties were evaluated; external chilling injury, electrolyte leakage, mass loss, firmness, respiration rate and peel colour. Results showed that selections and harvest seasons had no significant effect (P=0.668) on the moisture content of the evaluated ‘Fuerte-type’ avocado fruit. After withdrawal from low storage temperature, there was a significant interaction (P˂0.05) between selections and harvest seasons on external chilling injury and electrolyte leakage. Results further showed that external chilling injury correlated with electrolyte leakage during both harvest seasons. Treatment factors had no significant effect (P=0.997) on mass loss. Similarly, treatment factors had no significant effect (P=0.139) on firmness. However, selection ‘H287’ had hard skin with an average firmness of 83.44 densimeter units during ripening in both harvest seasons. Treatment factors were highly significant (P˂0.05) on respiration rate. Respiration rate followed a climacteric pattern and the magnitude of climacteric peak and day of occurrence varied amongst selections during both harvest seasons. Ripening percentage differed significantly (P˂0.05) amongst harvest seasons, selections and ripening days. Treatment factors had no significant effect on lightness (P=0.711), chroma (P=0.378) and hue angle (P=0.536) skin colour parameters,however, variations were recorded as a result of the cold damage black spots. The results indicated that the ‘Fuerte-type’ avocado selections had poor storage qualities. Further studies are required to evaluate physico-chemical properties during low storage temperature and the effect of season, production conditions and maturity level on development of chilling injury. In addition, studies on application of treatments to reduce chilling injury symptoms and analysis of bioactive compounds should be considered for conclusive recommendations. Thereafter, the selections can be planted in different production regions to assess and select the best producing and quality combinations for a given region as part of phase III of the project
Thesis (MSc. Agriculture (Horticulture)) -- University of Limpopo, 2016
Keywords: Avocado mass loss; Avocado physiological disorders; Avocado physico-chemical properties; Avocado electrolytes leakage; Avocado -- Harvesting -- South Africa